2011
DOI: 10.1007/s00248-011-9956-y
|View full text |Cite
|
Sign up to set email alerts
|

Protozoan Pulses Unveil Their Pivotal Position Within the Soil Food Web

Abstract: Protozoa are one of the most abundant groups of bacterivores within the soil and are responsible for mineralisation of bacterial biomass, having a large impact on C and N cycling. Little is known of their contribution to soil nutrient transfers or the identity of their consumers. Here, for the first time indigenous flagellates and ciliates, enriched to 83 atom% for (13)C and 10 atom% for (15)N, were introduced to soil cores from two different land managements, grassland and woodland with the same soil type, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 47 publications
0
34
0
2
Order By: Relevance
“…The δ 13 C and δ 15 N values were significantly different though, with those of the grassland being lower compared with the woodland ( δ 13 C F 1,10 = 86.10; P < 0.001 and δ 15 N F 1,10 = 43.09; P < 0.001; Table S1, other soil characters (Crotty et al (2012)).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The δ 13 C and δ 15 N values were significantly different though, with those of the grassland being lower compared with the woodland ( δ 13 C F 1,10 = 86.10; P < 0.001 and δ 15 N F 1,10 = 43.09; P < 0.001; Table S1, other soil characters (Crotty et al (2012)).…”
Section: Resultsmentioning
confidence: 95%
“…Collembola are generally considered to be fungivorous; however, studies have found them to consume large amounts of bacteria (Murray et al 2009; Crotty et al 2011) and protozoa (Crotty et al 2012). Subtle differences in the microbial community between habitats have the potential to affect the isotopic composition of a taxon, making it conceivable that they appear to be acting at different trophic levels dependent on habitat type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These experiments showed the movement of bacterial C and N through various invertebrate trophic levels, through the addition of an enriched culture of Pseudomonas lurida to form part of the bacterial feeding channel with results consistent across habitats (Crotty et al. ) and nutrient regimes (Murray et al. ).…”
mentioning
confidence: 74%